Performance anxiety, wellbeing, and cultural factors in Chinese music conservatories: a two-study research of student experiences - Bao, Huiqin; Yu, Lanying (Frontiers in Psychology, 2025)
IntroductionPerformance anxiety poses significant challenges for music conservatory students, especially in high-pressure educational contexts such as China. This research examined the link between performance anxiety and wellbeing, focusing on the moderating roles of perfectionism and collectivist orientation.MethodsStudy 1, using a correlational design with 1,364 students, assessed these relationships within the PERMA model. Study 2 employed an experimental design with 218 students randomly assigned to individual success, collaborative success, or neutral conditions.ResultsResults from Study 1 revealed that performance anxiety was negatively associated with wellbeing, with both perfectionism and collectivist orientation moderating this relationship. Study 2 showed that individual success conditions elicited the highest levels of anxiety, while collaborative settings offered partial support. Wellbeing outcomes were more complex: students in the individual condition reported higher wellbeing than those in the control group, whereas the collaborative condition did not differ significantly.DiscussionThese findings suggest that perfectionism can intensify anxiety in individual contexts, while collectivist orientation and collaborative performance settings may provide some protective effects depending on context. The study offers critical insights for music education and highlights the need to balance performance pressure, social support, and cultural factors when designing interventions to promote wellbeing among conservatory students.